Immunogenicity of a 2009 pandemic influenza virus A H1N1 vaccine, administered simultaneously with the seasonal influenza vaccine, in children receiving chemotherapy. Issue 6 (3rd January 2014) - Ottóffy, Gábor; Horváth, Petra; Muth, Lajos; Sólyom, Alexander; Garami, Miklós; Kovács, Gábor; Nyári, Tibor; Molnár, Dénes; Pauler, Gábor; Jankovics, István
<x xml:space="preserve">Abstract</x> Background No examination of simultaneous vaccination against pandemic H1N1 and the seasonal influenza virus strains, in children with cancer receiving chemotherapy, are yet published. We investigated the immunogenicity of a whole‐virion, inactivated, adjuvanted pandemic H1N1, and seasonal influenza vaccines administered simultaneously to children with cancer undergoing chemotherapy. Procedure We prospectively enrolled 27 pediatric patients receiving therapy for various types of cancer. All received influenza vaccination once in a seasonal risk period. We checked hemaglutination‐inhibition (HAI) antibody titers in the sera of patients before, and 21–28 days after vaccination. Seroprotective titer was defined as an antibody titer ≥40, and seroresponse as ≥4‐fold increase in antibody titers after vaccination. Results The pre‐ and post‐vaccination seroprotective rates were H1N1: 33–48%, H3N2: 56–78%, B: 0–15% for seasonal influenza, and for pandemic H1N1: 15–37%. The seroresponse rates for seasonal influenza H1N1, H3N2, and B were 22%, 37%, and 22%, respectively, and 30% for the pandemic H1N1 vaccine. Conclusions Whole‐virion, inactivated, adjuvanted vaccine for the pandemic H1N1 Influenza A virus and the seasonal influenza vaccines were found safe and partially immunogenic in children with cancer receiving chemotherapy. The only determinants of responsiveness were lymphocyte count and serum immunoglobulin‐G. Only influenza B vaccine elicited significant differences in differences in pre‐ and post‐vaccination seroprotective rates. The response to vaccination for pandemic H1N1 is as effective as other vaccines, however administration of a single vaccine during chemotherapy is more comfortable for pediatric cancer patients. Pediatr Blood Cancer 2014;61:1013–1016. © 2014 Wiley Periodicals, Inc.